2018
DOI: 10.20396/bjos.v17i0.8651901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of air-polishing on properties of nanocomposite submitted to coffee, red wine and cigarette smoke

Abstract: Aim: The aim of this study was to evaluate the surface roughness and the color stability of nanocomposite exposed to the sodium bicarbonate air-polishing (SBAP) followed by red wine, coffee and cigarette smoke exposure. Materials and Methods: 64 nanocomposite specimens were prepared and allocated in 8 groups: G1 (SBAP + distilled water), G2 (SBAP + coffee), G3 (SBAP + red wine), G4 (SBAP + cigarette smoke), G5 (distilled water), G6 (coffee), G7 (red wine) and G8 (cigarette smoke). The surface roughness was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…This finding was also confirmed by the same authors in a later study. 30 Conversely, Alandia-Roman et al 25 reported that finishing with abrasive papers prevented the color-change of a nano-hybrid to be clinically unacceptable (ΔE > 3.3). The control group, which was not polished, showed a color-change higher than the clinical acceptability threshold.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was also confirmed by the same authors in a later study. 30 Conversely, Alandia-Roman et al 25 reported that finishing with abrasive papers prevented the color-change of a nano-hybrid to be clinically unacceptable (ΔE > 3.3). The control group, which was not polished, showed a color-change higher than the clinical acceptability threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Among the possible factors responsible for staining, liquids and smoke are key factors. CS, as well as MRTP, may cause significant discoloration of RBCs determining the need of replacement 10,13,14,17,19,[24][25][26][27][28][29][30] . The possibility to simulate in vitro the staining susceptibility to smoke could be therefore of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Any disagreement was resolved by discussion. After full-text reading, 12 studies 10,13,14,17,19,[24][25][26][27][28][29][30] were included in the review (Fig. 1).…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations